Scanning electron microscope description of the afowo oil sand deposits in south-western nigeria (2011)
The Afowo oil sand deposits in parts of Southwestern Nigeria were described by scanning electron microscope for characterizing the reservoir sands, based on their clay content. Twelve core oil sand samples were collected, six of which were selected for analysis based onthe similarities in their physical and textural characteristics. The prepared oil sand samples were then described by scanning electron microscope studies (VEGA TESCAN/LMU scanning electron microscope-SEM).The analysis revealed that the oil sands contained minerals which had been precipitated and occurred as pore filling cement; these minerals included sheet kaolinite, vermiform kaolinite, k- feldspar, pyrite crystals, and corrosion quartz and corrosion feldspar. The SEM images also showed 2-4 µm micro pores and 2-5µm fractures.The study showed that the clay minerals contained in the Afowo formation's reservoir rocks were mainly kaolinite which was not expected to have any negative effects on reservoir quality, especially during enhanced oil recovery operations